2010
DOI: 10.1143/jjap.49.01ae10
|View full text |Cite
|
Sign up to set email alerts
|

A Glucose Sensor Based on an Organic Electrochemical Transistor Structure Using a Vapor Polymerized Poly(3,4-ethylenedioxythiophene) Layer

Abstract: A glucose sensor based on an organic electrochemical transistor (OECT) structure was prepared by vapor phase polymerization (VPP) of 3,4ethylenedioxythiophene (EDOT). The poly(3,4-ethylenedioxythiophene) (PEDOT) film was introduced as the conducting polymer channel and a platinum wire was used as a gate electrode in the OECT. The redox enzyme glucose oxidase (GOx) was introduced into the electrolyte of the OECT. The sensitivity and detection range of the sensor could be tuned by adjusting the source-drain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 24 publications
1
31
0
Order By: Relevance
“…Malliaras's group62, 86–95 has systematically investigated the OECTs for sensing applications. Zhu et al86 demonstrated a simple glucose sensor based on OECT at neutral pH.…”
Section: Sensors Based On Oectsmentioning
confidence: 99%
“…Malliaras's group62, 86–95 has systematically investigated the OECTs for sensing applications. Zhu et al86 demonstrated a simple glucose sensor based on OECT at neutral pH.…”
Section: Sensors Based On Oectsmentioning
confidence: 99%
“…Vapor-phase polymerization (VPP) has also been successfully used for the fabrication of OECTs-based glucose sensors by Kim et al [120] As reported in this paper, the authors prepared an oxidant solution containing Fe(III)-tosylate (dissolved in isopropyl alcohol) and spin-coated it on a glass substrate. The substrate was then placed inside a polymerization chamber containing a hot plate filled with a small amount of a 3,4-ethylenedioxythiophene (EDOT) solution.…”
Section: In-situ Polymerizationmentioning
confidence: 99%
“…Conducting polymer-based sensors can be classified by the nature of their detection methods such as amperometric, conductometric, chemiresistive, and others. 6,116 VPP conductive polymer films were first used for detecting 3 mM concentrations of alcohols (C 2 -C 4 ) by using patterned poly(3,3 0 -dipentoxy-2,2 0 -bithiophene) on nonconductive substrates like glass and surface oxidized silicon wafers. An increase in conductivity was detected in less than 5 s for all alcohols tested, and responses were observed to decrease as the chain length of the alcohol increased.…”
Section: Electrochromic Devicesmentioning
confidence: 99%
“…118 An amperometric glucose sensor based on VPP PEDOT was demonstrated, which showed a linear relationship between the response against micro-to mili-molar Figure 21(b). 116 Chemiresistive sensing properties of conductive polymers can be improved by covalent immobilization of an analyte specific molecule to the conducting polymer matrices. For example, direct analysis of the changes in the work functions of metal nanoparticles when exposed to a vapor is very difficult.…”
Section: Electrochromic Devicesmentioning
confidence: 99%